User Centered Iterative Design pada Front-End SPOTA UNTAN - Rahmadani, Dwisuci; Sastypratiwi, Helen; Perwitasari, Anggi (Universitas Negeri makassar, 2025)
The process of accepting Final Project (TA) topics and the interaction between students and lecturers are crucial in determining the quality of the final projects. The Final Project Outline Support System (SPOTA) UNTAN, introduced in 2008, still requires UI improvements to enhance User Experience (UX). This study aims to redesign the SPOTA UNTAN interface using the User Centered Iterative Design (UCID) method, focusing on user needs through repeated iterations. Usability Testing results with Task-Based Testing showed an improvement with a usability score of 97 and a System Usability Scale (SUS) score of 86.625, categorized as “B” with an “excellent” rating. Keywords: Web, UI/UX Redesign, User Centered Iterative Design (UCID), Usability Testing, System Usability Scale